"Be as You Are" Clinical Research Center at the Sapienza University of Rome. Issue 4 (2nd October 2019) - Baiocco, Roberto; Pistella, Jessica
Abstract: Italy's government has enacted few supportive policies for lesbian, gay, bisexual, transgender and all other sexual orientations and gender identities with which persons may identify (LGBTQ+), and most of the fundamental rights for sexual minorities are still not recognized. Despite this social and political situation, the Department of Developmental and Social Psychology of the Faculty of Medicine and Psychology, Sapienza University of Rome established "Be as You Are, " the first Italian clinical research center specifically created for LGBTQ + people on a university campus. The facility offers several public services, such as: (a) counseling or individual psychotherapy for LGBTQ + adolescents and young adults; (b) family therapy supporting LGBTQ + adolescents; (c) parent training programs; (d) interventions in different social contexts. This letter to the editor aims to present the clinical research center and to introduce the role played by LGBTQ + health care services to improve the well-being and mental health of sexual minority individuals, especially in stigmatized contexts where sexual prejudices are still rife, such as in Italy.